E-020 Aneurysms with the third cranial nerve palsy: long-term results of intentional sparing of daughter sac from coil packing. (23rd July 2017) - Lee, Y; Kwon, H; Koh, H
Abstract : Purpose: Aneurysms which cause oculomotor nerve [cranial nerve (CN) III] palsy are frequently found with a daughter sac of the aneurysm dome. We assumed that CN III might be compressed by the daughter sac and it would be more helpful not to fill the daughter sac with coils than vice versa during endosaccular embolization for recovering from CN III palsy, because it may give a greater chance for the daughter sac to shrink by itself later. We reviewed the long-term follow up results of our experiences of such cases. Methods: Among 17 aneurysms accompanied by CN III palsy, 13 (12 unruptured, 1 ruptured) showed a daughter sac along the long axis of the main dome. We tried to fill the main dome completely and spare the daughter sac from coil filling to maximize the decompression. We evaluated the initial and long-term effectiveness of this concept using medical records and follow-up images. Results: After initial embolization, all of CN III palsy caused by unruptured aneurysms (12/12) resolved completely after various periods (3–90 days) of time. No adverse effects were noted during and after the procedures except for one case of harmless coil stretching during coil filling using double microcatheter technique. One patient with ruptured aneurysm expired from lung problems after 2 months. Mean follow-up period is 49.8 months (3–96, median 75). Coil compaction was found in one aneurysm at 6 months and re-embolization was done. No symptom recurrence was noted during follow-up periods. Conclusion: During the coil embolization of the cerebral aneurysm causing CN III palsy, sparing the daughter sac from coil packing while tightly packing the main dome can be helpful in increasing the effectiveness of decompression. Disclosures: Y. Lee: None. H. Kwon: None. H. Koh: None.